Agricultural Property And Methods Of Exploitation In The Beylik Of The East Late Ottoman Era - Chibani, Hayet; Attia, Abdelkamel; Bedida, Lazhar (جامعة الوادي - University of Eloued, 2024)
This study falls within the topics of the economic field of Algeria during the Ottoman era, and through it we can identify the most important aspects of economic activity, and aspects of the daily life of the Algerian individual during this historical era, as this is a crucial period in the modern history of Algeria, the economic aspect had a direct and effective impact on various walks of life, and through this study we can reveal the most important pillars of economic activity, namely agricultural property. Despite the diversity and multiplicity of aspects of land ownership during the study period, despite the fertility of lands and the good location of many of them, we noticed that fertile and good lands were in the hands of the ruling power and had a good yield most of the time, part of them was directed for export, the rest of the lands were less fertile, less profitable, and most of the crop was directed towards domestic consumption
مقال
Keywords: property ; Agricultural ; beylik ; exploitation ; methods